The night she disappeared eaudiobook A novel. - Jewell, Lisa (Simon & Schuster Audio, 2021)
A 2022 Audie Award Finalist From the #1 New York Times bestselling author of None of This Is True comes "her best thriller yet" (Harlan Coben, New York Times bestselling author) about a young couple's disappearance on a gorgeous summer night, and the mother who will never give up trying to find them. On a beautiful summer night in a charming English suburb, a young woman and her boyfriend disappear after partying at the massive country estate of a new college friend. One year later, a writer moves into a cottage on the edge of the woods that border the same estate. Known locally as the Dark Place, the dense forest is the writer's favorite place for long walks and it's on one such walk that she stumbles upon a mysterious note that simply reads, "DIG HERE." Could this be a clue towards what has happened to the missing young couple? And what exactly is buried in this haunted ground? "Utterly gripping with richly drawn, hugely compelling characters, this is a first-class thriller with heart" (Lucy Foley, New York Times bestselling author) that will keep you on the edge of your seat.